The effectiveness of the buddy program training module to enhance the daily living function, social participation and emotional status of older adults in residential aged care homes - Adefolalu, Adegoke; Asmuri, Siti Noraini; Kadar, Masne; Razaob, Nor Afifi; Chui, Chai Siaw; Mohd Rasdi, Hanif Farhan (Public Library of Science, 2024)
Background The Compeer Model, which was originally designed to match individuals recovering from mental illness with volunteers from their community, served as the basis for the development of the buddy program. However, limited research was available related to the buddy program among older adults in a Malaysian context. Aim The study aimed to identify the effectiveness of the buddy program training module to enhance the daily living function, social participation and emotional status of older adults in residential aged care homes. Methods A quasi-experimental study was conducted with 30 pairs of buddies and older adults for both the experimental group and control group in two randomly selected residential aged care homes. The buddies in the experimental group received the buddy program training module related to activities of daily living (basic and instrumental) while the buddy-older adults pairs in the control group continued to perform their usual daily life activities in residential aged care homes. Baselines were performed before intervention and at eight weeks post-intervention. Results Over the eight weeks, for the older adults in the experimental group, there was a significant main effect of time after the intervention on BADL (p = 0.010). There were no significant interaction effects for the experiment group and control group on IADL and social participation. Also, there were no significant interaction effects for all domains in emotional status: depression, anxiety and stress. For buddies, there was a significant interaction effect for depression (p = 0.045) in the control group. Conclusions The buddy program training module can be used as a guideline for older adults with more significant disabilities in residential aged care homes in managing activities of daily living. Future studies could be implemented to explore the intergenerational buddy program among older adults and young children in the community. © 2024 Asmuri et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.